Multiple Barriers The Multilevel Governance of Homelessness in Canada - Smith, Alison (University of Toronto Press, 2022)
Despite decades of efforts to combat homelessness, many people continue to experience it in Canada's major cities. There are a number of barriers that prevent effective responses to homelessness, including a lack of agreement on the fundamental question: what is homelessness? In Multiple Barriers, Alison Smith explores the forces that shape intergovernmental and multilevel governance dynamics to help better understand why, despite the best efforts of community and advocacy groups, homelessness remains as persistent as ever. Drawing on nearly 100 interviews with key actors in Vancouver, Calgary, Toronto, and Montreal, as well as extensive participant observation, Smith argues that institutional differences across cities interact with ideas regarding homelessness to contribute to very different models of governance. Multiple Barriers shows that the genuine involvement of locally based service providers, with the development of policy, are necessary for an effective, equitable, and enduring solution to the homelessness crisis in Canada.